Effects of aggregation pheromone concentration and distance on the trapping of Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae) adults. (September 2020) - Dissanayaka, D.M.S.K.; Sammani, A.M.P.; Wijayaratne, L.K.W.; Rajapakse, R.H.S.; Hettiarachchi, S.; Morrison, W.R.
Abstract: Rhyzopertha dominica male adults produce an aggregation pheromone that attracts both sexes. While many studies have tested the behavioral response of R. dominica adults to its aggregation pheromone, information on the distance of attraction and effective pheromone concentration are lacking. Therefore, the objectives of this study were to determine the recapture rate of R. dominica adults released at different distances from a pheromone-baited and pheromone + kairomone-baited trap, as well as the most effective pheromone concentration for R. dominica . Experiments were arranged as complete randomized design with four replicates. A commercial pitfall trap containing R. dominica pheromone alone or pheromone + kairomone was placed inside an experimental arena. Adult R. dominica were released at different distances from the trap and the adults captured were counted. A separate experiment was conducted using pitfall traps containing different concentrations of the aggregation pheromone placed inside the experimental arena. Adult R. dominica were released 60 cm away from the pitfall trap and the recaptured adults were recorded. The trapping efficiency was higher when the trap contained both the pheromone and kairomone than the pheromone alone. Trap capture was highest when the beetles were released at distances up to 70 cm and at a concentration of 100 μL/1 m 2 . Our findings suggest that food facility managers should take into account the effective pheromone concentration and distance of attraction, while also strongly consider including food kairomones in traps when developing monitoring programs for R. dominica . Highlights: Rhyzopertha dominica adults were released at various distances from traps. Traps had pheromone (different concentrations) alone or together with kairomone. Pheromone + kairomone attracts more R. dominica adults than pheromone alone. Highest attraction of R. dominica occurs until 70 cm from pheromone. Pheromone at 100 μL/1 m 2 provides the maximum attraction of R. dominica adults.